Ethnicity, history and standard Ixhil (Ixil) Mayan. (July 2018) - Romero, Sergio
Abstract: This paper explores the tension between local ethnic identities and pan-Maya language ideologies in the development of Standard Ixhil Mayan, a standardized variety recognized by the Guatemalan state and the Academy of Mayan Languages of Guatemala. Based on the analysis of interviews and publications in Ixhil, I examine how alternative ethnic identities are indexed through variations in orthographic conventions. As in other Mayan communities in the highlands of Guatemala, standardization is a contested field in which different notions of indigeneity are staged. I discuss the role of systemic tensions between the Maya movement and Ixhil communities and show how local dialectal stereotypes are being used to forge a pan-linguistic Ixhil super-ethnicity capable of buttressing local spaces of cultural sovereignty. Highlights: Ixhil orthographic conventions embody an ideology in which image is a visual metaphor of ethnicity. The Ixhil literacy model indexes a plurality of ethnic identities but also enacts a shared communitas . Standard Ixhil simultaneously reconciles pan-dialectal unity and local practice.